Complete Genome Insights into Lactococcus petauri CF11 Isolated from a Healthy Human Gut Using Second- and Third-Generation Sequencing - Ou, Yun-Jing; Ren, Qiao-Qiao; Fang, Shu-Ting; Wu, Ji-Guo; Jiang, Yun-Xia; Chen, Yi-Ran; Zhong, Yi; Wang, De-Dong; Zhang, Guo-Xia (Frontiers in Genetics, 2020)
Lactococcus petauri CF11 was originally isolated from the gut of healthy humans. To determine the underlying molecular and genetic mechanisms of the probiotic potential of CF11, we performed complete genome sequencing, annotation, and comparative genome analysis. The complete genome of L. petauri CF11 comprised of 1,997,720 bp, with a DNA G+C content of 38.21 mol% containing 1982 protein coding genes and 16 rRNA operons. We found that 1206 genes (56.05%) were assigned a putative function using the Gene Ontology (GO) resource. The gene products of CF11 were primarily concentrated in molecular function and biological processes, such as catalysis, binding, metabolism, and cellular processes. Furthermore, 1365 genes (68.87%) were assigned an illative function using COGs. CF11 proteins were associated with carbohydrate transport and metabolism, and amino acid transport and metabolism. This indicates that CF11 bacteria can perform active energy exchange. We classified 1111 genes (56.05%) into six KEGG functional categories; fructose-bisphosphate aldolase and the phosphoenol pyruvate:phosphotransferase system (PTS), which are necessary in producing short-chain fatty acids (SCFAs), were excited in the carbohydrate metabolic pathway. This suggests that L. petauri CF11 produces SCFAs via glycolysis. The genomic island revealed that some regions contain fragments of antibiotic resistance and bacteriostatic genes. In addition, ANI analysis showed that L. petauri CF11 had the closest relationship with L. petauri 159469T, with an average nucleotide consistency of 98.03%. Taken together, the present study offers further insights into the function and potential role of L. petauri CF11 in health care.